2018
DOI: 10.1186/s12954-018-0224-z
|View full text |Cite
|
Sign up to set email alerts
|

Expanding harm reduction to include fentanyl urine testing: results from a pilot in rural British Columbia

Abstract: BackgroundHarm reduction has been at the forefront of the response to the opioid overdose public health emergency in British Columbia (BC). The unprecedented number of opioid overdose deaths in the province calls for an expansion of harm reduction services. The purpose of this study was to determine the acceptability of a fentanyl urine drug test among people who use drugs (PWUD) and explore whether testing introduced any changes in participants’ attitudes and behaviors towards their drug use.MethodsA pilot of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 4 publications
1
17
1
Order By: Relevance
“…This finding resonates with other studies in which trust has been identified as a key factor influencing access [41,[52][53][54]. We also heard how the most significant factor was that individuals involved be respectful regardless of if they identify as a person who uses drugs or not; this aligns with recent findings of a fentanyl test strip pilot project [55]. Moreover, given the high levels of trauma experienced as part of the overdose crisis, a trauma-informed approach [56] is required for service delivery.…”
Section: Discussionsupporting
confidence: 87%
“…This finding resonates with other studies in which trust has been identified as a key factor influencing access [41,[52][53][54]. We also heard how the most significant factor was that individuals involved be respectful regardless of if they identify as a person who uses drugs or not; this aligns with recent findings of a fentanyl test strip pilot project [55]. Moreover, given the high levels of trauma experienced as part of the overdose crisis, a trauma-informed approach [56] is required for service delivery.…”
Section: Discussionsupporting
confidence: 87%
“…Unlike similar Canadian studies , we found no evidence of fentanyl‐laced heroin through urine screens among people who inject ‘heroin’ in Sydney, Australia. Regarding feasibility and acceptability, clients appeared interested in whether their heroin contained fentanyl, as demonstrated among similar populations elsewhere . The instant urine tests were easy to use in a community health setting.…”
Section: Discussioncontrasting
confidence: 99%
“…Further work should establish the extent to which positive tests result in changes to substance use patterns. This is a promising area of inquiry: previous studies have found that point‐of‐care detection of fentanyl and analogues in drug samples (‘drug checking’) offers clients an opportunity to avoid consuming specific drug batches and increases reports of harm‐reducing practices .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations